Divergence of stem biomechanics and hydraulics between Bauhinia lianas and trees - Xiao, Yan; Song, Yu; Wu, Fu-Chuan; Zhang, Shu-Bin; Zhang, Jiao-Lin (AoB plants, 2021)
Liana abundance and biomass are increasing in neotropical and Asian tropical seasonal forests over the past decades. Stem mechanical properties and hydraulic traits influence the growth and survival of plants, yet the differences in stem mechanical and hydraulic performance between congeneric lianas and trees remain poorly understood. Here, we measured 11 stem mechanical and hydraulic traits for 10 liana species and 10 tree species from Bauhinia grown in a tropical common garden. Our results showed that Bauhinia lianas possessed lower stem mechanical strength as indicated by both modulus of elasticity and modulus of rupture, and higher stem potential hydraulic conductivity than congeneric trees. Such divergence was mainly attributed to the differentiation in liana and tree life forms. Whether the phylogenetic effect was considered or not, mechanical strength was positively correlated with wood density, vessel conduit wall reinforcement and sapwood content across species. Results of principle component analysis showed that traits related to mechanical safety and hydraulic efficiency were loaded in the opposite direction, suggesting a trade-off between biomechanics and hydraulics. Our results provide evidence for obvious differentiation in mechanical demand and hydraulic efficiency between congeneric lianas and trees. Liana abundance and biomass have increased in neotropical and Asian tropical seasonal forests over the past decades. Stem mechanical properties and hydraulic traits influence the growth and survival of plants, yet the differences in stem mechanical and hydraulic performance between congeneric lianas and trees remain poorly understood. Here, we measured 11 stem mechanical and hydraulic traits for 10 lianas and 10 trees from Bauhinia grown in a tropical common garden. Our results showed that a trade-off existed between stem biomechanics and hydraulics, which provide evidence for obvious differentiation in mechanical demand and hydraulic efficiency between congeneric lianas and trees.